2012
DOI: 10.1007/s10863-012-9461-0
|View full text |Cite
|
Sign up to set email alerts
|

Cataract-associated D3Y mutation of human connexin46 (hCx46) increases the dye coupling of gap junction channels and suppresses the voltage sensitivity of hemichannels

Abstract: Connexin46 (Cx46), together with Cx50, forms gap junction channels between lens fibers and participates in the lens pump-leak system, which is essential for the homeostasis of this avascular organ. Mutations in Cx50 and Cx46 correlate with cataracts, but the functional relationship between the mutations and cataract formation is not always clear. Recently, it was found that a mutation at the third position of hCx46 that substituted an aspartic acid residue with a tyrosine residue (hCx46D3Y) caused an autosomal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…In this study, we show that substitution of a polar tyrosine at residue 3 for the negatively charged aspartic acid present in wild-type Cx46 results in a rightward shift in the activation curve and appears to disrupt hemichannel closure at positive potentials. In another recent report, Schlingmann et al (29) found that this same D3Y substitution in human wild-type Cx46 resulted in the lack of voltage-sensitive hemichannels when expressed in Xenopus oocytes. The macroscopic gating properties of Cx46D3Y hemichannels resemble those previously reported for Cx46D3N.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In this study, we show that substitution of a polar tyrosine at residue 3 for the negatively charged aspartic acid present in wild-type Cx46 results in a rightward shift in the activation curve and appears to disrupt hemichannel closure at positive potentials. In another recent report, Schlingmann et al (29) found that this same D3Y substitution in human wild-type Cx46 resulted in the lack of voltage-sensitive hemichannels when expressed in Xenopus oocytes. The macroscopic gating properties of Cx46D3Y hemichannels resemble those previously reported for Cx46D3N.…”
Section: Discussionmentioning
confidence: 91%
“…Several mechanisms have been proposed to account for the role of these mutations in the development of disease: 1) inability to form functional gap junctions; 2) alterations in the gating and permeability properties of gap junctions; 3) dominant negative effects on other connexins; 4) aberrant hemichannel activity; and 5) mistrafficking leading to cytoplasmic accumulation of protein. With a few exceptions (20,29,34), most of the cataract-associated connexin mutations that have been studied are unable to form gap junctional plaques when expressed by themselves and show mistrafficking (2-4, 7, 19, 24, 25, 32, 42). Some of them also act as dominant negative inhibitors of wild-type connexin activity.…”
mentioning
confidence: 99%
“…Also, it is becoming increasingly clear that Cxs have profound effects on gene expression during the process of development. Gap junction-deficient and -mutant mice present a range of debilitating phenotypes, such as hereditary diseases of the lens (zonular pulverulent cataract) (18), nervous system (X-linked Charcot-Marie-Tooth disease) (19), hereditary non-syndromic deafness (20), skin (palmoplantar keratoderma) (21), and bone and teeth (occulodigitoldental dysplasia) (22). These are additional reasons that altered expressions of gap junction proteins in injured human corneas require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…It is unknown whether these changes in the permeability properties correlate with structural rearrangements of the NT inside the pore. A number of mutations at the NT have been shown to affect selectivity of small molecules, voltage dependence and unitary conductance, expected if the NT is folded within the pore (Xin et al, 2010; Beyer et al, 2012; Schlingmann et al, 2012; Xin and Bai, 2013). …”
Section: Voltage Gatingmentioning
confidence: 99%